On the thermodynamic stability of nanocrystalline ceramics - Castro, Ricardo H.R. (Materials letters, 2013)
Nanomaterials have intrigued the scientific community for many years due to their unique and unexpected properties. Though the number of technological applications has impressively increased in the past years, a fundamental understanding of the behavior of nanomaterials is still incomplete. This is particularly true from a thermodynamic viewpoint, which defines the nanostructure overall thermal stability, polymorphism, and is ultimately connected to an optimal exploitation and reliability of the nano-features. This short review presents recent advancements on the understanding of the energetics of nanocrystalline ceramics and how they relate to nanoscale stability phenomena by focusing on the latest experimental evidences. The role of interface energetics as a key instrument to enable stability prediction and control is discussed based on a quantitative description of nanoscale phase diagrams and coarsening processes. Techniques to assess interface energies of ceramic nanostructures are also briefly discussed, in particular addressing the highly sensitive calorimetric methods recently used to acquire unprecedented interface energy data for oxides. A short collection of experimental evidences and trends on the thermodynamic understanding of nanocrystalline oxides, focusing on aluminum oxide, titanium dioxide, zirconium oxide, and tin dioxide, concludes this review. ► The thermodynamics of nanoceramics is addressed, focusing on the quantitative description of the effects of interface energies on phenomena such as phase stability and coarsening.► The usage of dopants prone to interface segregation is formally described as a tool to enable interface energy control and, consequently, improve nanostability. ► The techniques required to assess interface energetics of nanoceramics are also addressed.